Monte Carlo simulation and experimental validation of the Finapp Model 3 cosmic-ray neutron sensor - Vykydal, Zdenek; Šolc, J; Rusňák, J; Blahušiak, P; Vlk, P; Köhli, Markus; Millán-Callado, M A; Zbořil, M (Measurement science and technology, 2026)
This work summarizes reference measurements, Monte Carlo (MC) particle transport modeling, and validation of the Finapp Model 3 cosmic-ray neutron sensor (CRNS). The MC calculations and reference measurements were performed independently in the broad-range radionuclide reference neutron fields of Czech Metrology Institute and Slovak Institute of Metrology. The validated model outputs were subsequently verified using monoenergetic neutron reference fields with energies ranging from 24 keV to 1.2 MeV at the Physikalisch-Technische Bundesanstalt, Germany, confirming the predicted response agreement within 13% of the experimental results. To demonstrate the applicability of the validated and verified models, they were used to predict the probe behavior in a virtual reference neutron field simulating realistic conditions with relative volumetric soil moisture levels ranging from 1% to 50%. The obtained results matched the Universal Transport Solution model across the whole soil moisture range. Single parameter power equation which, together with on-site calibration, can be used to convert the relative count rate of the Finapp 3 probe to volumetric soil moisture is proposed.
Veröffentlicht: 17. Dezember 2025
Gesehen am 09.02.2026